Mengukur pengaruh kualitas layanan model CARTER terhadap kepuasan nasabah perbankan syariah Indonesia - Abu Amar Fauzi (Journal of Business & Banking, 2016)
Sharia banking in Indonesia continues to grow from year to year and there are currently 12 sharia commercial banks and 22 sharia business units of conventional banks. However, the market share of sharia banking is still less than 5% of the market share of conventional banking. This phenomenon proves that the existence of sharia banking on a dual banking system that runs in Indonesia is still a shadow of conventional banking. By using a CARTER model consisting of the dimensions of compliance, assurance, reliability, tangible, empathy, and responsiveness, this research is directed to explore the perception of customers to service quality dan its influence on customer satisfaction of sharia banking in Indonesia. Structural Equation Model (SEM) based on nonlinear regression techniques partial least square (PLS) on WarpPLS 5.0 is used to analyze the data obtained from a survey of 97 customers of Bank Muamalat Indonesia in Surabaya. These results indicate that the service quality of sharia bank has a significant relationship with customer satisfaction. Empathy has the most powerful influence on customer satisfaction of sharia bank. Yet, compliance becomes the lowest dimension of service quality that affects customer satisfaction in Indonesia sharia banks.